First occurrence of a Hymenosomatid crab Elamena mathoei (Desmarest, 1823) (Crustacea: Decapoda: Brachyura) in the Mediterranean Sea - ZAOUALI, J.; BEN SOUISSI, J.; RIFI, M.; D'UDEKEM d'ACOZ, C. (Mediterranean Marine Science, 2013)
Mediterranean fauna is undergoing drastic modifications as a result of anthropogenic activities and global warming. The most important of these is the colonization of the Mediterranean Sea by alien species, many of them entering through the Suez Canal. While many of them are still confined to the Levant Basin, several have extended their distribution westwards to Tunisian waters. The presence of the Indo-west Pacific hymenosomatid crab Elamena mathoei on a rocky shore at Sidi Daoud, Cape Bon Peninsula, Tunisia, is the first Mediterranean record of this species. It is a testimony to the changes in the patterns of invasion in the Mediterranean Sea.